Effects of genotype and sex on carcass composition, meat quality, digestive tract morphometries and leg bone dimensions of spent parent Pekin ducks - Marcin Wegner; Dariusz Kokoszyński; Joanna Żochowska-Kujawska; Marek Kotowicz (Poultry Science)
The purpose of the present study was to analyze carcass composition, physicochemical properties, muscle texture, and structure, as well as morphometry of the digestive tract and leg bone dimensions of Cherry Valley ducks (SM3 Heavy hybrid) and Orvia ducks (ST5 Heavy hybrid) after laying. A total of 32 ducks were dissected, 8 females and 8 males from each breeding set. Analysis of meat quality (breast muscle, leg muscle) in terms of color (L*, a*, b*), acidity (pH24), electrical conductivity (EC24), and basic chemical composition (protein, water, fat, collagen) was performed. Analysis of the texture and structure of the pectoral muscle was also performed. The dimensions of the various lengths of the digestive tract and the dimensions of the tibia and femur were analyzed. Cherry Valley ducks after laying have better slaughter performance and a higher proportion of breast muscle in the carcass (P < 0.001). Also more favorable chemical composition (protein, fat, water) and physical properties (acidity, electrical conductivity, thermal loss) of muscle. In terms of texture characteristics, the pectoral muscle of Cherry Valley ducks was more elastic and cohesive, but also more flexible with higher viscosity, while the pectoral muscles of Orvia ducks in terms of structure were characterized by smaller values of the analyzed characteristics (cross-sectional area of fibers and smaller vertical and horizontal diameter). Analyzing the morphometry of the digestive system, Orvia ducks were characterized by longer sections of the digestive tract, which certainly has a beneficial effect on the absorption of nutrients. In terms of tibia and femur measurements taken, there were no differences between genotypes, while males were characterized by higher values of the analyzed traits compared to females.